1986
DOI: 10.1139/f86-224
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Phytoplankton Composition of 95 Labrador Lakes, with Special Reference to Natural and Anthropogenic Acidification

Abstract: Phytoplankton abundances and accompanying morphometric, physical, and chemical data from 95 Labrador lakes were subjected to statistical analysis to determine the structure of the phytoplankton communities and to relate environmental factors to the patterns observed. Factor analysis of the 22 measured physical and chemical variables reduced the data to six derived environmental factors: hardness, dystrophy, lake size, salinity, oligotrophy, and seasonality. The analysis showed that the low-pH lakes are associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…These factors may be responsible for elevated phytoplankton parameters of the Bolshezemelskaya tundra relative to Western Siberia thaw ponds (54-158 taxa; 0.3-54 mg wet .L x1 biomass of the former). Similar number of phytoplankton species was reported for lakes of Finland (Heinonen, 1980) and the Labrador Lakes (Earle and Duthie, 1986): 52-62 and 61, respectively.…”
Section: Comparison With Other Arctic and Subarctic Lakessupporting
confidence: 81%
“…These factors may be responsible for elevated phytoplankton parameters of the Bolshezemelskaya tundra relative to Western Siberia thaw ponds (54-158 taxa; 0.3-54 mg wet .L x1 biomass of the former). Similar number of phytoplankton species was reported for lakes of Finland (Heinonen, 1980) and the Labrador Lakes (Earle and Duthie, 1986): 52-62 and 61, respectively.…”
Section: Comparison With Other Arctic and Subarctic Lakessupporting
confidence: 81%
“…The boreal forested regions in Canada (Earle et al 1986), the United States (Driscoll and Newton 1985;Baker et al 1991), and northern Europe (Braake et al 1987) contain an abundance of waters with low pH and high organic acidity. Many species of odonates are noted to utilize these bog-pond environments extensively (Walker and Corbet 1975;Hilton 1987).…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with those of other studies. For example, factor analysis of 22 abiotic parameters of 95 Labrador lakes reduced data to six factors including hardness (especially alkalinity, calcium, and magnesium) and dystrophy (especially dissolved organic carbon and color) (Earle et al, 1986). Based on the PCA ordination of 73 small shallow lakes in Wisconsin, Dodson et al (2005) reported three axes including parameters associated with aquatic vegetation; variables related to the water source, water color, nutrient concentrations (positively) and conductivity (negatively).…”
Section: Large Scale Correlates Of Lacustrine Diversitymentioning
confidence: 99%